Mathematical Model of the Process of Hiding Cotton Fiber From Saw Teeth - Khusanova Shahida Alibek's Qizi; R.Shermatova; X.Axmatqulova; M.Sayfiddinova (Genius Publishing Group, 2022)
It is known that the issue of maintaining the initial quality of cotton products in the process of sawing is relevant. The main reason for this is that the ginning process is carried out with strong impact effects on the raw material.
Keywords: Break; cut; result; seed